We Salute the Allied Armies : Great Concert Meeting (leaflet) (1941)
034-0056-001 We salute the ALLIED ARMIES! GREAT CONCERT MEETING SATURDAY, 20th SEPT. CAMBRIDGE THEATRE -3 p.m.- PROGRAMME SYMPHONY ORCHESTRA and MASSED CHOIR Conducted by GEOFFREY CORBETT EGMONT OVERTURE (Beethoven) DANCES FROM "PRINCE IGOR" (Borodin) ENGLISH, POLISH AND RUSSIAN SONGS MARCH FROM 6th SYMPHONY (Tschaikowsky) YOUNG CZECHOSLOVAKIA WALTER HUDD. BEATRIX LEHMANN FAMOUS SPEAKERS will probably include Lt.-Col. HANS KAHLE QUENTIN REYNOLDS WILFRID ROBERTS, M.P. W. ROWE Col. JOSIAH WEDGWOOD Major S. WILD HELP OUR COMRADES IN THE CONCENTRATION CAMPS TICKETS: 1/6, 3/-, 5/-, all bookable in advance from I.B.A., 58 Theobalds Road, W.C.1. HOLborn 2583 INTERNATIONAL BRIGADE ASSOCIATION Printed by the London Caledonian Press Ltd (T.U. all Depts.), 74 Swinton Street, W.C.1-9316 292/946/34/56